Gas supply reliability assessment of natural gas transmission pipeline systems. (1st November 2018) - Yu, Weichao; Song, Shangfei; Li, Yichen; Min, Yuan; Huang, Weihe; Wen, Kai; Gong, Jing
Abstract: The uncertainty of market demand and dynamic behaviour of the pipeline system are usually ignored in previous gas supply reliability assessments. With the intent of overcoming these deficiencies, a novel methodology to assess the gas supply reliability of natural gas transmission pipeline systems is proposed in this paper. Considering both gas supply capacity and market demand uncertainties, calculations of these two items are integrated into a single Monte Carlo simulation. On each Monte Carlo trial, the hydraulic analysis of unsteady flow is combined with the state transition process simulation to calculate the gas supply capacity. In terms of market demand, the load duration curve technology is employed to predict the amount of demand. Then, the indicator proposed to quantify gas supply reliability is calculated on each trial. Finally, the average gas supply reliability is obtained based on N Monte Carlo trials. Applications of this methodology are demonstrated through a real transmission pipeline system. Thereafter, the method is compared with previous approaches and differences are discussed. Furthermore, the impacts of supply capacity and market demand uncertainties on the gas supply reliability are investigated and suggestions to improve the gas supply reliability are proposed. Highlights: A methodology to assess gas supply reliability of pipeline systems is proposed. Demand uncertainty and system's dynamic behaviour are considered. A real pipeline system is adopted to demonstrate the feasibility of methodology. The impacts of supply capacity and market demand uncertainties are investigated.